The risk of inappropriate timing of complementary foods introduction is increased among first-time mothers and poor households - Puspitorini Puspitorini; Prasetya Lestari; Bunga Astria Paramashanti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Background: Global recommendations suggest mothers provide the first complementary food to infants when they reach six months of age. Failure to introduce complementary foods promptly may put infants in adverse health and nutrition outcomes. Objective: This study aimed to analyze factors associated with inappropriate timing of complementary foods introduction in Kebumen Regency. Methods: This study used a cross-sectional design. A multistage cluster sampling was employed to select 355 mothers of children aged 6-23 months in Kebumen Regency. Our dependent variable was the timing of complementary food introduction. Meanwhile, independents variables included factors at the child, parental, and household levels. Univariate and multiple logistic regressions were performed in this study. Results: There was 39.15% of young children received inappropriate timing of complementary feeding. Being the second-born child or above (OR=0.56; 95%CI: 0.33-0.95) and coming from high-income households (OR= 0.57; 95%CI: 0.36-0.90) were protective factors of inappropriate timing of complementary foods introduction. Other variables such as maternal age, maternal education, maternal occupation, father’s education, and family support were not significantly associated with incorrect timing of complementary feeding. Conclusions: The proportion of inappropriate timing of complementary foods introduction in Kebumen Regency is alarming and is mainly explained by child’s birth rank and household economic status suggesting the importance of targeting nutritional education to first-time mothers as well as poor households.